Attractiveness of black rhinoceros (Diceros bicornis) to tsetse flies (Glossina spp.) (Diptera: Glossinidae) and other biting flies - Mihok, S.; Moloo, S.K.; Oden'y, J.O.; Brett, R.A.; Rakwar, J.G.; Munyoki, E.; Kiilu, J.; Kyorku, C.A. (Cambridge University Press, 1996)
Druing translocations of black rhinoceros (Diceros bicornis Linnaeus) in Kenya, we studied the relationships between the rhinoceros and biting flies. In trapping experiments, rhinoceros waste products (urine or dung) were substituted for known attractants such as cow urine, 1-octen-3-ol or acetone. Catches of Glossina pallidipes Austen, Glossina longipennis Corti, Stomoxys spp., and Haematopota spp. were not affected by these substitutions. NG2G and Vavoua traps sited near captive animals caught similar numbers and kinds of flies as traps set without animals. Any minor attractive properties of rhinoceros odours were probably due to the presence of known attractants such as 4-cresol and 3-n-propylphenol, which were confirmed to be present through gas chromatography-mass spectroscopy. In feeding trials with laboratory-reared tsetse, Glossina brevipalpis Newstead and Glossina morsitans centralis Machado fed well on immobilized animals, whereas G. longipennis fed reluctantly. Catches of G. brevipalpis were doubled in one trapping experiment when rhinoceros urine was used as odour bait. Philoliche spp., Haematopota spp. and other Trabanidae fed on captive rhinoceroses. Many species of Stomoxyinae were associated with rhinoceroses. Of these, the most frequent association was with Rhinomusca dutoiti Zumpt, a species found previously only in South Africa. Rhinomusca dutoiti was found in two highland rhinoceros sanctuaries, Nairobi National Park and Solio Ranch Game Reserve.